A STUDY OF JOB SATISFACTION OF COLLEGE LIBRARIAN WORKING IN THE ACADEMIC AFFILIATED COLLEGES IN THE DISTRICT OF AKOLA MS (International Journal of Food and Nutritional Sciences, 2022)
This study looked for librarians for job satisfaction as librarians working in an academic college located in the Akola district of Maharashtra, India. A self-constructed job satisfaction questionnaire was developed and used to measure the job satisfaction of librarians working in academic colleges of Akola district. Data were collected from 50 academic college libraries. The study revealed that librarians do not feel anxious about fulfilling their duties and responsibilities in this profession. The study found that college librarians have varying levels of job satisfaction and are highly satisfied with their jobs. College libraries have the highest levels of customer satisfaction. However, academics are not satisfied with some academy management policies that focus on their own problems. This course is useful for planning, making decisions, developing a professional library workforce, good library and information services, developing a good organizational environment in college libraries and information centers, and developing business plans.